Cooperative regulation of light-harvesting complex II phosphorylation via the plastoquinol and ferredoxin-thioredoxin system in chloroplasts - Rintamäki, E. (The National Academy of Sciences, 2000)
Light induces phosphorylation of photosystem II (PSII) proteins in chloroplasts by activating the protein kinase(s) via reduction of plastoquinone and the cytochrome b(6)f complex. The recent finding of high-light-induced inactivation of the phosphorylation of chlorophyll a/b-binding proteins (LHCII) of the PSII antenna in floated leaf discs, but not in vitro, disclosed a second regulatory mechanism for LHCII phosphorylation. Here we show that this regulation of LHCII phosphorylation is likely to be mediated by the chloroplast ferredoxin–thioredoxin system. We present a cooperative model for the function of the two regulation mechanisms that determine the phosphorylation level of the LHCII proteins in vivo, based on the following results: (i) Chloroplast thioredoxins f and m efficiently inhibit LHCII phosphorylation. (ii) A disulfide bond in the LHCII kinase, rather than in its substrate, may be a target component regulated by thioredoxin. (iii) The target disulfide bond in inactive LHCII kinase from dark-adapted leaves is exposed and easily reduced by external thiol mediators, whereas in the activated LHCII kinase the regulatory disulfide bond is hidden. This finding suggests that the activation of the kinase induces a conformational change in the enzyme. The active state of LHCII kinase prevails in chloroplasts under low-light conditions, inducing maximal phosphorylation of LHCII proteins in vivo. (iv) Upon high-light illumination of leaves, the target disulfide bond becomes exposed and thus is made available for reduction by thioredoxin, resulting in a stable inactivation of LHCII kinase.